Partisipasi Anggota Kelompok Wanita Tani (KWT) dalam Program Pekarangan Pangan Lestari (P2L) Di Kabupaten Klaten - Khasanah, Rahmadani; Suminah, Suminah; Widiyanti, Emi (Universitas Muhammadiyah Semarang, 2024)
The P2L program is an effort to increase the availability, accessibility, and diversity of food, oriented towards increasing household income and welfare. Participation is one indicator of the success of a program. As time goes by, the participation of KWT members decreases. The research aims to analyze the participation level of KWT members, analyze the socio-economic conditions (non-formal education, type of work, income level, yard area and social environment) of KWT members receiving the P2L Program in Klaten Regency, and analyze the influence of KWT members' socio-economic factors on the level of their participation in the P2L Program in Klaten Regency. The basic research method is quantitative with survey techniques. The research location was deliberately determined in Klaten Regency. The sampling method was proportional random sampling technique, with a sample of 66 respondents. Data analysis uses multiple linear regression tests. The research results show that the level of participation at the planning stage and monitoring and evaluation stage is low, while the implementation and results utilization stage is high. Non-formal education is in the high category, social environment is in the very high category, while type of work, income level and yard area are in the low category. Non-formal education, income level and social environment influence the level of participation of KWT members while type of work and size of yard land have no influence.